EFEITO DO TRÁFEGO CONTROLADO DE MÁQUINAS EM DIFERENTES SISTEMAS DE PREPARO DO SOLO - OLIVEIRA, Débora Cristina Sousa Barros de; SILVA, Fagner Luiz Rodrigues; GUIMARÃES JUNNYOR, Wellingthon da Silva; SANTOS, Maria Aparecida Do Nascimento; MARTINS, Murilo Battistuzzi (ANAIS DO ENIC, 2024)
-